Rethinking irrigation modernisation: realising multiple objectives through the integration of fisheries - McCartney, Matthew P.; Whiting, L.; Makin, I.; Lankford, B.A.; Ringler, Claudia (Commonwealth Scientific and Industrial Research Organisation, 2019)
Irrigation has been, and will remain, instrumental in addressing water security (Sustainable Development Goal (SDG) 6), food insecurity (SDG 2) and poverty (SDG 1) goals. However, the global context in which irrigation takes place is changing rapidly. A call for healthier and more sustainable food systems is placing new demands on how irrigation is developed and managed. Growing pressures from competing water uses in the domestic and industrial sectors, as well increasing environmental awareness, mean irrigation is increasingly called on to perform better, delivering acceptable returns on investment and simultaneously improving food security, rural livelihoods and nutrition, as well as supporting environmental conservation. Better integration of fisheries (including aquaculture) in irrigation planning, investment and management can contribute to the modernisation of irrigation and the achievement of the multiple objectives that it is called on to deliver. A framework illustrating how fisheries can be better integrated with irrigation, and how the two can complement each other across a range of scales, from scheme to catchment and, ultimately, national level, is presented.